Utilization of Animated Videos as Microteaching Media to Increase Student Learning Interest - Adam Supyadin; Euis Latipah; Aliman Alfalah; Deden Abdurahman (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
Microteaching is a small-scale teaching practice designed to enhance the pedagogical competence of prospective teachers. Through this activity, education students develop skills in lesson planning, material delivery, and learning evaluation. One critical aspect of microteaching is the selection of appropriate and engaging learning media tailored to student characteristics. This article aims to examine the use of animated videos as a medium in microteaching and its effect on students’ learning interest. This study employs a descriptive-reflective method based on the direct experience of students conducting microteaching in a guided academic setting. Observations revealed that the use of animated videos created a more interactive, visual, and enjoyable learning environment. Students showed higher focus, enthusiasm, and participation during lessons delivered with animated content compared to conventional methods. Beyond its positive effect on students, animated video media also increased the confidence and creativity of student-teachers in delivering learning materials. This type of media allows them to present abstract concepts more concretely through easily understandable visual illustrations. These findings align with previous research, which indicates that visual media significantly improves student motivation and academic performance. Therefore, animated videos are not only effective in microteaching contexts but also serve as innovative instructional tools in actual classroom practice. This article recommends the use of animated videos as a modern learning innovation that integrates technology with student learning needs effectively.